THE EFFECT OF HYBRID LEARNING AND ENJOYMENT LEARNING IN INCREASING ADVANCED MATHEMATICAL THINKING - Ayu Aristika; Darhim Darhim; Dadang Juandi; Kusnandi Kusnandi (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
Abstract AMT ability is one of the skills that is a priority to be developed in learning mathematics in universities. This research aims to test the effect of hybrid learning and enjoyment learning in improving Advance Mathematical Thinking of prospective teacher students moderated by learning style. This research is a quantitative research that aims to examine the effect of the independent variable on the dependent variable. The sample in this study is conducted by purposive sampling based on certain criteria. The research data is obtained by distributing questionnaires to the mathematics education program student at University X in Bandung City. The data collected is analyzed by path analysis assisted by Smart PLS application. Smart PLS analysis in this study is carried out in 2 stages which are the analysis of the outer model and the inner model. Analysis of the inner model is aimed at (1) testing the validity and reliability of the instrument and (2) performing the r-square test to determine the percentage of influence. The test results show that learning enjoyment and hybrid learning have a significant positive effect on advanced mathematics learning. The learning styles in this study have not been able to moderate the relationship between hybrid learning and enjoy learning on Advance Mathematical Thinking. Hybrid learning can be used as an alternative or learning solution in improving advanced mathematical learning.Keywords: hybrid learning, Advance Mathematical Thinking, enjoyment learning, prospective teacher students, learning style Abstrak Kemampuan AMT merupakan salah satu kemampuan matematis yang menjadi prioritas untuk dikembangkan dalam pembelajaran matematika di perguruan tinggi. Penelitian Ini Bertujuan Untuk Menguji Pengaruh Hybrid Learning dan Enjoyment Learning Dalam Meningkatkan Berpikir Advance Mathematical Thinking of Prospective Teacher Students dimoderasi Gaya Belajar. Penelitian ini merupakan penelitian kuantitatif yang bertjuan untuk menguji pengaruh variabel independen terhadap variabel dependen. Sample dalam penelitian ini dilakukan dengan purposive sampling dengan berdasarkan beberapa kriteria tertentu. Data penelitian diperoleh dengan menyebar quesioner pada mahasiswa program studi Pendidikan Matematika di Universitas X di Kota Bandung. Data yang terkumpul dianalisa dengan analisis path berbantuan aplikasi Smart PLS. Analisis smart PLS pada penelitian ini dilakukan dengan 2 tahapan yaitu analisa outer model dan inner model. Analisa inner model untuk 1) menguji validitas dan reliabilitas instrumen serta 2) melakukan uji r square untuk mengetahui presentase pengaruh. Hasil pengujian hipotesis menunjukkan bahwa enjoyment learning dan Hybrid learning berpengaruh secara positif signifikan terhadap Advance mathematic learning. Adapun, gaya belajar dalam penelitianini belum mampu memoderasi hubungan hybrid learning dan enjoyment learning terhadap Advance Mathematic Thinking. Hybrid learning dapat dapat dijadikan alternatif atau solusi pembelajaran dalam meningkatkan Advance Mathematic Learning. Kata kunci: pembelajaran hibrid, Advance Mathematical Thinking, kenikmatan belajar, mahasiswa calon guru, gaya belajar